Microbial electrosynthesis of acetate from CO2 under hypersaline conditions - Xiaoting Zhang; Tyler Arbour; Daijun Zhang; Shiqiang Wei; Korneel Rabaey (Environmental Science and Ecotechnology, 2023)
Microbial electrosynthesis (MES) enables the bioproduction of multicarbon compounds from CO2 using electricity as the driver. Although high salinity can improve the energetic performance of bioelectrochemical systems, acetogenic processes under elevated salinity are poorly known. Here MES under 35–60 g L−1 salinity was evaluated. Acetate production in two-chamber MES systems at 35 g L−1 salinity (seawater composition) gradually decreased within 60 days, both under −1.2 V cathode potential (vs. Ag/AgCl) and −1.56 A m−2 reductive current. Carbonate precipitation on cathodes (mostly CaCO3) likely declined the production through inhibiting CO2 supply, the direct electrode contact for acetogens and H2 production. Upon decreasing Ca2+ and Mg2+ levels in three-chamber reactors, acetate was stably produced over 137 days along with a low cathode apparent resistance at 1.9 ± 0.6 mΩ m2 and an average production rate at 3.80 ± 0.21 g m−2 d−1. Increasing the salinity step-wise from 35 to 60 g L−1 gave the most efficient acetate production at 40 g L−1 salinity with average rates of acetate production and CO2 consumption at 4.56 ± 3.09 and 7.02 ± 4.75 g m−2 d−1, respectively. The instantaneous coulombic efficiency for VFA averaged 55.1 ± 31.4%. Acetate production dropped at higher salinity likely due to the inhibited CO2 dissolution and acetogenic metabolism. Acetobacterium up to 78% was enriched on cathodes as the main acetogen at 35 g L−1. Under high-salinity selection, 96.5% Acetobacterium dominated on the cathode along with 34.0% Sphaerochaeta in catholyte. This research provides a first proof of concept that MES starting from CO2 reduction can be achieved at elevated salinity.